Formation of information culture of future specialists: strategic guidelines of the modern educational paradigm (Pedagogy of Higher and Secondary Education, 2022)
The problem of necessity of formation of the contemporary young educated man’s informational culture has been revealed. The article stresses on importance of informational culture high level, which stimulates the improvement of training process provides the availability & effective ness of educational process.
Keywords: culture; information culture; information’s society